2022
DOI: 10.3389/fphar.2022.817662
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Adverse Events Associated With Immune Checkpoint Inhibitors: A Large-Scale Pharmacovigilance Analysis

Abstract: Backgrounds: Immune checkpoint inhibitors (ICIs) are considered cornerstones of oncology treatment with durable anti-tumor efficacy, but the increasing use of ICIs is associated with the risk of developing immune-related adverse events (irAEs). Although ICI-associated pancreatic adverse events (AEs) have been reported in patients treated with ICIs, the clinical features and spectrum of pancreatic AEs are still not well-defined. Therefore, this study aimed to identify the association between pancreatic AEs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In 35,223 patients from 50 RCTs, the all-grades PI incidence was 2.22% (95% CI = 1.94–2.53%), which was less than previous similar studies ( George et al, 2019 ; Su et al, 2018 ; Zhou et al, 2021 ). This study aligns with previous studies ( George et al, 2019 ; Su et al, 2018 ; Zhang et al, 2022 ; Petrelli et al, 2021 ) and confirms that the incidence of PI with combined ICI use is significantly higher than that of single ICI. Furthermore, a previous study exploring the safety of more than 2 ICIs suggested that the incidence of elevated lipase was as high as 7.2% (95% CI = 5.2–9.9) ( Zhou et al, 2021 ), which is significantly higher than these results.…”
Section: Discussionsupporting
confidence: 92%
“…In 35,223 patients from 50 RCTs, the all-grades PI incidence was 2.22% (95% CI = 1.94–2.53%), which was less than previous similar studies ( George et al, 2019 ; Su et al, 2018 ; Zhou et al, 2021 ). This study aligns with previous studies ( George et al, 2019 ; Su et al, 2018 ; Zhang et al, 2022 ; Petrelli et al, 2021 ) and confirms that the incidence of PI with combined ICI use is significantly higher than that of single ICI. Furthermore, a previous study exploring the safety of more than 2 ICIs suggested that the incidence of elevated lipase was as high as 7.2% (95% CI = 5.2–9.9) ( Zhou et al, 2021 ), which is significantly higher than these results.…”
Section: Discussionsupporting
confidence: 92%
“…To some extent, such difference is largely attributed to the fact that immune‐mediated pancreatitis is the unique toxic effect of ICIs on the pancreas, which lead to the aggregation of ICIs‐related AE reports in the PT of immune‐mediated pancreatitis ( Figure ) and the corresponding increase of signal strength. The toxic effect of ICIs is different from other drug classes in that it specifically enhances immune responses by promoting T lymphocyte activity systematically, thereby facilitating a range of autoimmune toxicity potentially against pancreas and resulting in irreversible lesions (e.g., type 1 diabetes mellitus caused by autoimmune attack on pancreatic cells) and other potentially life‐threatening conditions 41 . Due to the wide application of ICIs at present and the great harm of pancreatic AEs, it is necessary to comprehensively understand the detailed safety profile of ICIs induced AP for further prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Although some antineoplastic agents, such as immune checkpoint inhibitors (ICIs), L-asparaginase (or pegaspargase), and vascular endothelial growth factor receptor tyrosine kinase inhibitors, are known to significantly increase the risk of AP, [37][38][39] the quantity proportion of antineoplastic agents are not obviously predominant in the list of drugs summarized based on ADR reporting systems or literature review. [16][17][18][20][21][22][23][24][25]36 In our opinion, this discrepancy may be mainly attributed to the development and clinical application of novel antitumor drugs in recent years and the gradually recognized AP risk of it, 37,[39][40][41] whereas our research opportunely caught a glimpse of the emerging risk role of antineoplastic agents in inducing AP due to incorporating the real-time AP risk information of drugs. Furthermore, in order to further summarize the distribution characteristics of AP culprit-drugs, we made statistics on the top 10 drugs and drug classes with the highest reporting quantity proportion at the SMQ level and PT level (Figures 3, 4), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the disproportionality analysis was used to analyze the safety data of semaglutide to quantitative gastrointestinal positive signals based on FAERS database, which was a global, public and accessable pharmacovigilance database ( 14 , 15 ). Further, stratification analysis, clinical priority of signals, time-to-onset, and the serious outcomes were performed to detect the characteristics of semaglutide-associated gastrointestinal AEs.…”
Section: Introductionmentioning
confidence: 99%